2020
DOI: 10.3390/diagnostics10100767
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Method Complex Approach for Hydration Assessment Does Not Detect a Hydration Difference in Hemodialysis versus Peritoneal Dialysis Patient

Abstract: Assessment of hydration status is essential in monitoring the effectiveness of renal replacement therapy and is usually based on physical examination. However, comparisons of hydration status achieved with different dialysis methods are not conclusive. We compared the hydration status of patients on chronic hemodialysis (HD, n = 60) and peritoneal dialysis (PD, n = 20) in a comprehensive assessment including physical examination and additional methods. The mean age of the 80 chronically dialyzed patients (53 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Similarly, in a smaller study including 65 hemodialysis and 52 PD patients, eccentric LVH was more common only in overhydrated hemodialysis patients compared to the total PD patients [33]. In a more recent study comparing hydration status, measured with lung ultrasound, vena cava diameter, bioimpedance analysis, and N ‐terminal pro‐brain natriuretic peptide, between 60 hemodialysis and 20 PD unmatched patients, results showed no significant differences between groups in any of the volume‐related parameters, whereas LVMi was marginally higher in hemodialysis compared to the PD group (181.59 [range: 108.72–382.28] vs. 150.99 [range: 106.47–256.70]; p = 0.063) [34]. A case‐control study including 22 hemodialysis and 24 PD patients has found no significant differences in the prevalence of LVH (77% vs. 71%), as well as in LVMi (149 ± 40 vs. 134 ± 32 g/m 2 ), LVEDD (4.91 ± 0.59 vs. 5.04 ± 0.66), and LA diameter (3.70 ± 0.50 vs. 4.03 ± 0.54) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a smaller study including 65 hemodialysis and 52 PD patients, eccentric LVH was more common only in overhydrated hemodialysis patients compared to the total PD patients [33]. In a more recent study comparing hydration status, measured with lung ultrasound, vena cava diameter, bioimpedance analysis, and N ‐terminal pro‐brain natriuretic peptide, between 60 hemodialysis and 20 PD unmatched patients, results showed no significant differences between groups in any of the volume‐related parameters, whereas LVMi was marginally higher in hemodialysis compared to the PD group (181.59 [range: 108.72–382.28] vs. 150.99 [range: 106.47–256.70]; p = 0.063) [34]. A case‐control study including 22 hemodialysis and 24 PD patients has found no significant differences in the prevalence of LVH (77% vs. 71%), as well as in LVMi (149 ± 40 vs. 134 ± 32 g/m 2 ), LVEDD (4.91 ± 0.59 vs. 5.04 ± 0.66), and LA diameter (3.70 ± 0.50 vs. 4.03 ± 0.54) [35].…”
Section: Discussionmentioning
confidence: 99%
“…The examination typically includes a blood pressure measurement and assessments of the presence and severity of peripheral edema and the detection of crackles over the pulmonary fields. However, these assessments are not sufficient to make a reliable assessment of the degree of fluid overload [19][20][21]. Moreover, it remains challenging to assess the correct hydration status in patients that require dialysis.…”
Section: Is the Nature Of Overhydration The Same In Hf And Ckd?mentioning
confidence: 99%
“…Moreover, it remains challenging to assess the correct hydration status in patients that require dialysis. Consequently, the medical examination results are objectified with additional methods; for example, the whole body electrical bioimpedance can be measured; ultrasound can be performed to assess inferior vena cava compliance; or ultrasound can be performed to assess pulmonary congestion [21]. Each of these methods has advantages and limitations (Table 1).…”
Section: Is the Nature Of Overhydration The Same In Hf And Ckd?mentioning
confidence: 99%